Fractional-like Hukuhara derivative and its properties - Martynyuk, A.A. (Reports of the National Academy of Sciences of Ukraine, 2019)
The concept of fractional-like Hukuhara derivative for set-valued maps is introduced, its properties are discussed, and the principle of comparison is established for fractional-like set-valued differential equations.